Dietary knowledge, attitude and practices of diabetic patients at Nsambya Hospital Kampala, Uganda - Ntaate, Conrad (Stellenbosch : University of Stellenbosch, 2016)
Thesis (MFamMed)--Stellenbosch University, 2015.